The therapeutic potential of Nelumbo Nucifera against oxidative damage induced by Carbon Tetrachloride in rats. - Bibi, Sagheera; Naz, Lubna (International Journal of Endorsing Health Science Research, 2022)
Background: Herbal treatment has paid much attention in the world over the past decades. Nelumbo nucifera is used all over the world as a medicinal plant. It is an aquatic perennial plant belonging to the Nelumbonaceae family. The protective effects of Nelumbo nucifera are due to the active ingredients present in it. The study was conducted to evaluate the protective effects of Nelumbo nucifera seeds against hepatotoxicity caused by carbon tetrachloride (CCl4) in rats. Methodology: Eighteen Wistar Albino rats were allotted into three groups (n=6), control group, CCl4 treated group given CCl4 0.8 ml/kg body weight subcutaneously twice a week, CCl4 + N. Nucifera treated group given CCl4 0.8 ml/kg body weight 2 times a week subcutaneously and also given Nelumbo nucifera extract (200 mg/kg body weight) orally through gavage daily. After 28 days of the experiment, serum samples were taken for estimation of enzyme activities and liver tissue samples were collected for evaluation of antioxidant enzyme levels. Results: It was observed that liver weight increased in the CCl4 treated group while liver weight decreased in CCl4 + N. Nucifera treated group. CCl4 administration significantly raises the transaminase levels such as Aspartate transaminase (AST) (p<0.01), Aspartate transaminase (ALT) (p<0.05), and Alkaline phosphatase (ALP) (p<0.05) whereas CCl4 + N. Nucifera treated group serum transaminases are reduced. Antioxidant activities such as Catalase (p>0.05), Glutathione (GSH) (p>0.05) and Superoxide dismutase (SOD) (p=0.05) decreased in the CCl4 treated group. Significant elevation of antioxidant enzymes; Catalase (p<0.05), GSH (p<0.05) and SOD (p>0.05) in CCl4 + N. Nucifera treated group. Serum Malondialdehyde (MDA) concentration (p<0.05) significantly raised in the CCl4 hepatotoxic group compared to the control group. A decreased MDA levels were observed in the CCl4 + N. Nucifera treated group, indicating its potential to counteract the harmful effects of CCl4. Conclusion: This study suggests that Nelumbo nucifera seeds have overcome CCl4-induced hepatotoxicity by their antioxidant effects.